‚Die albanische Mauer‘ Grenzbegriffe im Albanischen (Altre Modernità, 2021)
This article explores border terms in Albanian using the example of theDibra region. Dibra is an Albanian-Macedonian border region that originally formed acultural, linguistic-dialectal and (extended) family unit and developed manifolddivergences with the drawing of the borders in 1913 resp. 1925, including borderterms. The article elaborates a great linguistic diversity to express spatial demarcationsuntil the drawing of state borders at the beginning of the 20th century on a nationalbasis, which was very foreign to local cultures. Therefore, no existing term provedsuitable to express the new type of demarcation – the state borders. The locallanguages or dialects – in this case Dibra – still developed a number of new terms,most of which were borrowed. However, it also integrated the German term Mauer(‚wall‘) by means of a loan translation. This is because the borders of the state ofAlbania are perceived by the Albanians in a similar way to the German-German borderas an internal national border that was drawn unjustly and therefore had to fall like itsmodel in Berlin. The analysis of border terms in this article traces this developmentwith the help of historical sociosemantics.
Keywords: border terms; state borders; albanian; Dibra; Socio-semantics